O engajamento e o processo de relacionamento interno mediado pela comunicação nas organizações - Bem, Júlio César de (2013)
Organizations are undergoing changes due to new demands regarding social relationships while also seeking results not merely restricted to economic and financial aspects. Changes are more encompassing, involving the human dimension of communication, as a mediator of relationships in the organizational environment. This calls for greater concern from the upper management of organizations in strengthening the role of internal communication, within its range of spheres, segments and visions, involving strategic alignment, integration and interaction. It matters as it creates a perspective of media, the intensity and flow of communication, both in the instrumental aspect and the human and strategic. The human dimension requires special attention, which is not entirely acknowledged in organizations (Kunsch, 2010). Effective management of internal communication in the human dimension, based on conserving the solidity of relationships, implies in the effective engagement of employees with the organization. The leading objective of this study was to identify the engagement factors of people, considering the internal relationship mediated by communication in organizations. As such, a social-type study was developed, using an empirical base, involving the methodological procedures of research-action in a large private organization, leader in its segment in the southern region of Brazil. Based on the study, the following factors were identified: internal communication processes that place value on human relationships, leadership, organizational identification processes, performance assessment and appreciation of people. Thus, there is a noted need to place greater value on communication as a means of strengthening the engagement of people in an organization as a base in its human relationships, especially through the role of its leaders in the workplace.